Studies on the Physiology of Digestion in the last Instar Larva of the Rice Moth (Corcyra cephalonica Stainton) I. pH of the alimentary Canal (Lepidoptera: Galleriidae). - Srivastava, P. N. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The hydrogenion concentration of the fore- and mid-gut of Corcyra larva is strongly alkaline (8.4-9.4) and that of the hind-gut weakly acidic (6.0-6.8). The acidity in the hind-gut is due to the mixing of the acidic contents of the Malpighian tubules. pH of the gut is not dependent upon the type of food of insect. Insects of the same family also differ in their pH.